2009
DOI: 10.1176/appi.ajp.2008.07101681
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Neural Habituation in the Amygdala and Social Impairments in Autism Spectrum Disorders

Abstract: These results suggest amygdala hyperarousal in autism spectrum disorders in response to socially relevant stimuli. Further, sustained amygdala arousal may contribute to the social deficits observed in autism spectrum disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
195
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(218 citation statements)
references
References 40 publications
19
195
1
3
Order By: Relevance
“…Histological studies also showed numerical reductions in amygdala axons (Schumann & Amaral, 2006) and reduced cell sizes in the hippocampus, similar to what is seen in the case of a precocious maturation (Bauman & Kemper, 2005). The two cerebral formations are involved in emotional and memory process development, two aspects typically targeted by autism spectrum disorders (Kleinhans et al, 2009;Saitoh et al, 2001). The use of MRI-DTI for the microstructural analysis of pathways interconnecting hippocampus and amygdala with the mid-fusiform gyrus in the temporal lobe (which participates in number, word, color and physiognomy recognition) revealed dysfunctionalities of these connections in autistic subjects which took a face recognition test (Conturo et al, 2008).…”
Section: Wwwintechopencomsupporting
confidence: 61%
“…Histological studies also showed numerical reductions in amygdala axons (Schumann & Amaral, 2006) and reduced cell sizes in the hippocampus, similar to what is seen in the case of a precocious maturation (Bauman & Kemper, 2005). The two cerebral formations are involved in emotional and memory process development, two aspects typically targeted by autism spectrum disorders (Kleinhans et al, 2009;Saitoh et al, 2001). The use of MRI-DTI for the microstructural analysis of pathways interconnecting hippocampus and amygdala with the mid-fusiform gyrus in the temporal lobe (which participates in number, word, color and physiognomy recognition) revealed dysfunctionalities of these connections in autistic subjects which took a face recognition test (Conturo et al, 2008).…”
Section: Wwwintechopencomsupporting
confidence: 61%
“…6,7,11 Moreover, in another study, participants with ASD and controls both showed amygdala activation in response to faces, but the ASD participants showed less habituation in the amygdala. 47 To build a coherent model of ASD and brain function, it is important that aspects of the task, such as the cognitive elements and habituation rates, be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Kleinhans et al (2009) showed that repeated exposure to faces resulted in significantly reduced activation of the amygdala in typical adults but this neural adaptation was attenuated in adults with autism. Additional research is needed to clarify whether differences in face adaptation are also observed in relatives of children with autism in both the amygdala and other key ''face areas'' (e.g., the fusiform gyrus) and how they relate to behavioural performance in face processing tasks.…”
Section: Discussionmentioning
confidence: 99%